Quantitative assessment of gait parameters in people with Parkinson's disease in laboratory and clinical setting: Are the measures interchangeable? - Massimiliano Pau; Federica Corona; Roberta Pili; Carlo Casula; Marco Guicciardi; Giovanni Cossu; Mauro Murgia (MDPI AG, 2018)
This study aimed to investigate possible differences in spatio-temporal gait parameters of people with Parkinson's Disease (pwPD) when they are tested either in laboratory using 3D Gait Analysis or in a clinical setting using wearable accelerometers. The main spatio-temporal gait parameters (speed, cadence, stride length, stance, swing and double support duration) of 31 pwPD were acquired: i) using a wearable accelerometer in a clinical setting while wearing shoes (ISS); ii) same as condition 1, but barefoot (ISB); iii) using an optoelectronic system (OES) undressed and barefoot. While no significant differences were found for cadence, stance, swing and double support duration, the experimental setting affected speed and stride length that decreased (by 17% and 12% respectively, P<0.005) when passing from the clinical (ISS) to the laboratory (OES) setting. These results suggest that gait assessment should be always performed in the same conditions to avoid errors, which may lead to inaccurate patient's evaluations.